Chronic Kidney Disease Progression Risk in Patients With Diabetes Mellitus Using Dihydropyridine Calcium Channel Blockers: A Nationwide, Population-Based, Propensity Score Matching Cohort Study - Lin, Shih-Yi; Lin, Cheng-Li; Lin, Cheng-Chieh; Hsu, Wu-Huei; Hsu, Chung-Y.; Kao, Chia-Hung (Frontiers in Pharmacology, 2022)
Background: Whether diabetes mellitus (DM) patients with chronic kidney disease (CKD) can glean individual renal benefit from dihydropyridine calcium channel blockers (DCCBs) remains to be determined. We conducted a nationwide, population-based, propensity score matching cohort study to examine the effect of DCCBs on CKD progression in DM patients with CKD. Methods: One million individuals were randomly sampled from Taiwan’s National Health Insurance Research Database. The study cohort consisted of DM patients with CKD who used DCCBs. The comparison cohort was propensity-matched for demographic characteristics and comorbidities. The endpoint was advanced CKD or end-stage renal disease (ESRD). The Cox proportional hazards model was used to calculate the risks. Results: In total, 9,761 DCCB users were compared with DCCB nonusers at a ratio of 1:1. DCCB users had lower risk of advanced CKD and ESRD than nonusers—with adjusted hazard ratio (aHR; 95% confidence interval [CI]) of 0.64 (0.53–0.78) and 0.59 [95% CI, 0.50–0.71] for advanced CKD and ESRD, respectively. DCCB users aged ≥65 years had the lowest incidence rates of advanced CKD and ESRD—with aHR (95% CI) of 0.47 (0.34–0.65) and 0.48 (0.35–0.65) for advanced CKD and ESRD, respectively. Finally, cumulative DCCB use for >1100 days was associated with the lowest advanced CKD and ESRD risks (aHR, 0.29 [95% CI, 0.19–0.44]). Conclusion: DM patients with CKD who used DCCBs had lower risk of progression to advanced CKD and ESRD than nonusers did.